P35 Long-term remission is achievable in autoimmune hepatitis using Tacrolimus or Mycophenolate mofetil and results in regression of fibrosis. (6th September 2011) - Scott, R; White, J; Atwal, G; Taylor, N; Mortimore, G; Freeman, J; Lawson, A; Austin, A
Abstract : Introduction: 10–20% of patients do not respond to conventional treatment of autoimmune hepatitis, or are intolerant of azathioprine. There is no established second line treatment. Experience with transplant immunosuppressive agents such as Tacrolimus (TAC) and mycophenolate mofetil (MMF) is limited to small numbers and short-term follow-up. Aim: To describe the progress of all patients who had failed conventional therapy and were treated with second line agents with at least 12-month follow-up. Method: An audit of patients identified who received second line agents for at least 12 months on maintenance dose <10 mg prednisolone. Patient records were reviewed and treatment endpoints based on aminotransferase changes defined as; Complete response (CR) - sustained normalisation for at least 12 months, partial response (PR) - improvement by >50% but not always normal over a 12-month period. Where applicable, interval histology was reviewed by a single pathologist to assess ISHAK fibrosis scores at the start and at least 18 months after commencing second line agents. Results: A total of 26 patients were identified. 9 were treated with TAC for a median 81 months (21–137), 16 with MMF for a median 81 months (30–114) and one on a combination of TAC and MMF. Median age is 56 (28–68) and 64 (40–79) respectively. The median dose of TAC is 3.5 mg/day (1–6) and MMF 1 g/day (1–2). All patients on TAC achieved CR. Two patients discontinued treatment; one renal impairment and one rationalising treatment after 27 months CR. 11/16 patients on MMF achieved CR, 5/16 achieved PR. Five patients no longer take MMF; two due to toxicity (recurrent chest infections at 60 months, GI disturbance at 78 months), one successfully withdrew treatment after 39 months CR, one switched to TAC as a treatment failure of MMF after 103 months and one was withdrawn after a diagnosis of larynx SCC. The combination patient achieved CR and has received 50 months dual treatment with confirmed histological remission. Four patients on TAC and five on MMF had interval biopsies. 3/4 patients on TAC (median 87 months) exhibited stable or reduced grades of fibrosis compared to 2/5 patients on MMF (median 101 months). Conclusion: Effective long-term maintenance of remission at 10 years is achievable on MMF and TAC in the absence of significant toxicity. Achieving prolonged CR seems to confer disease control and can result in histological regression of fibrosis.